High‐Frequency Observations of Temperature and Dissolved Oxygen Reveal Under‐Ice Convection in a Large Lake. Issue 24 (23rd December 2017) - Yang, Bernard; Young, Joelle; Brown, Laura; Wells, Mathew
Abstract: Detailed observations of thermal structure over an entire winter in a large lake reveal the presence of large (10–20 m) overturns under the ice, driven by diurnal solar heating. Convection can occur in the early winter, but the most vigorous convection occurred near the end of winter. Both periods are when our lake ice model suggest thinner ice that would have been transparent. This under‐ice convection led to a deepening of the mixed layer over time, consistent with previous short‐term studies. During periods of vigorous convection under the ice at the end of winter, the dissolved oxygen had become supersaturated from the surface to 23 m below the surface, suggesting abundant algal growth. Analysis of our high‐frequency observations over the entire winter of 2015 using the Thorpe‐scale method quantified the scale of mixing. Furthermore, it revealed that changes in oxygen concentrations are closely related to the intensity of mixing. Key Points: Under‐ice convection plays an important role in the transport of dissolved oxygen in a deep lake at the end of winter Thorpe‐scale analysis reveals large convection cells whose timing is correlated to increases in oxygen Thorpe‐scale analysis distinguishes between periods of active mixing and homogenous mixed conditions